Design considerations for the tooth shoe shape for high-speed permanent magnet generators - Zhang, He; Zhang, Xiaochen; Gerada, C.; Galea, Michael; Gerada, David; Li, Jing (IEEE, 2015)
This paper presents a study of the effects that the shoe shape of the teeth of electrical machines has on the performance and losses. This is done by considering a concentrated wound, high-speed permanent magnet generator. The paper investigates the influence of the tooth shoe shape on the machine magnetic circuit and the losses distribution based on analytical and finite-element analysis (FEA). A shape coefficient Kt is proposed to provide an optimized design reference. A comprehensive analytical tool able to study the variations of the machine performance parameters is proposed. The deduced optimization function is normalized using the non-equilibrium relative weighting method, and then, it is processed via a genetic algorithm to achieve the optimized design. FEA is used to validate the proposed analytical tool and the optimum design.